Komunikasi Simbolik dalam Penggunaan Upakara Yajña pada Ritual Hindu - Tary Puspa, Ida Ayu; Sinta Dewi, Ni Putu; Subrahmaniam Saitya, Ida Bagus (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2019)
Hindus in carrying out rituals by way of karma and devotional service use ceremonial means called upakara or also called banten. Upakara presented to Ida Sang Hyang Widhi Wasa and its manifestations must be based on sincerity which is also adjusted to the level of yajña that can be carried out by Hindus both at the level of Nista, masdya, and the main.In the process of making and offering upakara there is symbolic communication, namely the symbol of devotion to God / Ida Sang Hyang Widhi Wasa by sparking gratitude to Him. Symbolic communication is communication that uses symbols that have been agreed upon by the community or a certain group. The message will have the same meaning if it is in accordance with the agreement set by a certain community.Every communication process that is interwoven between individuals with one another means becomes the main element. Whereas language has a very strategic position and the mind becomes a very significant thing in identifying and interpreting a symbolIn the yajña or bebantan upakara there are several principles which are principle, namely the principle of name or designation, it can also be the sound equation in the material of the bull itself. The principle of this name means that the elements of the bull when viewed from the name or sound contain the meaning that is in accordance with the purpose of the upakara.